Desenvolvimento de sistema IoT microcontrolado para monitoramento e acionamento de carga de baixa potência - Pereira, Lucas de Oliveira (2021)
With the technological evolution of recent times and the increase in the amount of electrical equipment in a residence, products based on the IoT concept and smart home are being increasingly sought after in the market, thanks to its advantages as tools that enable control and monitoring of equipment with offline architecture. In this context, it is believed that controlling, monitoring and making available information on instant energy consumption of electrical equipment to the residential user can serve as a way to make energy consumption more aware and even enable the saving of electricity in a home. Therefore, the present work aims at the development of a microcontrolled IoT system for real-time control and monitoring of electrical current consumption applied to low power equipment. The proposed system aims at remote control of connected load drives and the creation of estimated reports of individual energy consumption of each monitored device. With this, the system will allow the calculation of the estimated cost with the amount to be paid in relation to the local kWh rate for the period of operation of the load. The project is based on a circuit responsible for measuring electrical current using the ACS712 5 A current sensor and a load drive circuit using the Relé device. After obtaining the values, these signals are conditioned with the help of the ESP8266 microcontroller, processor core of the system software and communication with the web, which will perform the calculations of the samples in the defined period and control the activation of the device Relé (triggered via web control panel). Monitoring and trigger history data is transmitted to the MQTT server and mysql database. The system, in turn, has a web application that synchronizes in real time with the database server showing instant aninstant information of the electrical charge, drive history and estimated calculations, in addition to presenting controls for remote activation of the electrical charge. The Web Control Panel is based on Node.JS, MQTT, HTML, Vue.JS and CSS technologies. The result of this project is a complete system for monitoring and firing low-power electrical load, composed of hardware and software, with the prototype obtaining current values with average error less than 4% compared to an existing Chinese brand smart outlet on the market, and with an average response time of less than 3 seconds for activation and synchronization.